Illicit trade, economic growth and the role of Customs: a literature review - Mashiri, Eukeria; Sebele-Mpofu, Favourate Y. (International Network of Customs Universities, 2021)
Many developing economies depend heavily on trade-related taxes for their economic wellbeing and wealth creation. The growth in international trade, increase in the number of travellers, advances in technology and changes in trading methods have set new challenges for governments — challenges that require a change in the functioning of customs and border management if these offices are to function effectively and efficiently. This research paper furthers our understanding of the impact of illicit trade on economic growth, an important area of customs enquiry which has received little attention in prior studies. The study seeks to identify options for improving customs activities in order to maximise the detection of revenue leakage, while maintaining trade facilitation. The study analyses the extant literature and uses cross-country data to gauge the effect of illegal imports on economic growth. In light of limited information on the value of illicit trade due to its very nature, the analysis was restricted by the availability of data. Nevertheless, the findings show that illegal economic activity distorts local economies and reduces legitimate business and tax revenues. The paper concludes that the costs of illicit trade are not only economic but also have social implications, as illicit trade undermines the social stability and socioeconomic welfare of communities, preventing the equitable sharing of public goods. Further, it was found that Customs is a high risk area in which corrupt officials can facilitate duty evasion, causing significant financial damage to the government’s budget and to the economic stability of compliant traders. The review highlights the need for improved customs practices and suggests areas for further research.